2019
DOI: 10.1186/s12891-019-2467-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic ability of the German version of the STarT Back tool: analysis of 12-month follow-up data from a randomized controlled trial

Abstract: Background Stratified care is an up-to-date treatment approach suggested for patients with back pain in several guidelines. A comprehensively studied stratification instrument is the STarT Back Tool (SBT). It was developed to stratify patients with back pain into three subgroups, according to their risk of persistent disabling symptoms. The primary aim was to analyse the disability differences in patients with back pain 12 months after inclusion according to the subgroups determined at baseline us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
1
11
0
1
Order By: Relevance
“…Of these, 17 studies assessed pain and disability prognosis with univariate models 70 , 74 , 77 , 80 , 81 , 84 86 , 89 , 94 , 96 , 97 , 104 – 108 . Of the univariate analyses, eight showed significant prognostic benefits for pain intensity 74 , 83 , 85 , 89 , 93 , 97 , 106 , 107 , 13 showed significant prognostic benefits for disability 74 , 83 86 , 89 , 93 , 94 , 96 , 97 , 102 , 105 , 108 , while two showed significant prognostic benefits on mixed pain intensity and disability analyses 80 , 81 . Of the multivariate models, two studies showed the STarT Back to predict prognosis for pain intensity adjusted for baseline pain 90 , 91 , while four showed no significant association 71 , 72 , 78 , 93 .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Of these, 17 studies assessed pain and disability prognosis with univariate models 70 , 74 , 77 , 80 , 81 , 84 86 , 89 , 94 , 96 , 97 , 104 – 108 . Of the univariate analyses, eight showed significant prognostic benefits for pain intensity 74 , 83 , 85 , 89 , 93 , 97 , 106 , 107 , 13 showed significant prognostic benefits for disability 74 , 83 86 , 89 , 93 , 94 , 96 , 97 , 102 , 105 , 108 , while two showed significant prognostic benefits on mixed pain intensity and disability analyses 80 , 81 . Of the multivariate models, two studies showed the STarT Back to predict prognosis for pain intensity adjusted for baseline pain 90 , 91 , while four showed no significant association 71 , 72 , 78 , 93 .…”
Section: Resultsmentioning
confidence: 96%
“…the trajectory of a condition based on certain subgroup factors) of people with LBP, it is critical to account for the patients' pain and disability when they are first assessed, as these factors are the strongest and most consistent predictors of pain and disability in the months after LBP incidence [147][148][149][150] . The STarT Back tool was typically (in six 71,72,83,90,93,102 of eight 78,91 studies and 2080 of 2634 patients) able to predict future disability, but this was less consistent for pain intensity (two 90,91 of six 71,72,78,93 studies and 348 of 1899 patients). For the McKenzie method, no studies assessed the effectiveness of the classification method on future pain intensity while accounting for baseline values.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations